New idea of development movement coordination abilities in water of high level athletes practicing selected combat sports - Markiewicz, G.; Starosta, W. (Journal of Combat Sports and Martial Arts, 2014)
Achieving significant success in wrestling requires a high level of movement co-ordination abilities. In wrestling these abilities should be developed at the same time with strength abilities, because of them the success on the mat depends on. Reserves relating to the ways and means of developing movement coordination abilities become very quickly exhausted. Standard training conditions of wrestlers have been recently slightly changed, and water environment has been introduced. Hence, the aim of the investigations herewith was to: establish the effect of the special set of movement coordination complex exercises performed by wrestlers in natural and in water environment. Material and methods. The experiment was carried out with 31 wrestling champions (athletes of master class), who were divided into two groups: the control group and experimental group. Training session of each of the groups comprised a set of exercises developing movement coordination. Wrestlers from the control group (n=16) performed a set of movement coordination complex exercises. In the experimental group (n=15) an analogical set was used but performed in water with three kinds of body submerging: at the water surface, under the water and on the bottom of the swimming-pool. Technical elements and fragments of fights were performed during the training. The ability to maintain balance was evaluated in two ways: in the vertical and horizontal body position. The balance keeping (s) was assessed on a decreased support surface, and with eyes closed. The attempts were affected in the natural environment and in water. Results. The results of the researches showed an improved movement coordination as a consequence of the performed set of proposed exercises. The time of maintaining vertical position was longer than when performing attempts in horizontal position, and that applied both to attempts in natural conditions, as well as in water. Conclusions. In order to develop movement coordination among those practicing combat sports, it is suggested that exercises in a swimming-pool with various kinds of body submerging should be applied during training sessions (e.g. with wrestlers). This specific and versatile environment enables competitors to obtain immediate information serving the evaluation of the results of future reactions.